Pengaruh Promosi, Inovasi Produk, dan Harga Terhadap Keputusan dalam Membeli Produk Jejahits Id (Survei pada Konsumen Produk Jejahits.Id) - David Romadhon; Sunarso (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to investigate the influence of promotion, product innovation, and price on purchase decisions among consumers of Jejahits.id, a local fashion brand established in 2023 in Sukoharjo Regency. The study adopted a quantitative approach, collecting primary data through questionnaires from 100 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression, which yielded the following regression equation: Y=11.680+0.554X1 +0.216X2 −0.112X3. The partial test (t-test) results indicated that promotion and product innovation have a significant influence on purchase decisions, whereas price was found to have no significant effect. Furthermore, the coefficient of determination (R2) test revealed that the independent variables promotion, product innovation, and pric collectively account for 50.7% of the variance in purchase decisions. The remaining 49.3% is explained by other factors outside the research model, such as service quality, consumer satisfaction, and brand image.